The Optimal Mix Of The Objectives Of Commercial Banks Using Linear Programming - An Analytical Study In The National Islamic Bank - Dr. Hayder Adnan Ghanawi , Nibras Mohammed Abbas & Pro. Suaad A. F., (International Journal of Innovative and Applied Finance, 2023)
login and register and pay the fees to get open access to content